PATIENT SAFETY AWARENESS AMONG DENTAL STUDENTS IN LAHORE, PAKISTAN: A MULTI-CENTRE STUDY - Tufail, shazia; Shehla Baqai; Mustafa, Nilofar; Kamran, Rizwana; Tirmazi, Sobia Masood; Ahmed, Arub (Journal of Ayub Medical College Abbottabad, 2022)
Background: Awareness of key issues associated with patient safety is vital for improving patient care in all fields of medical sciences including dentistry. This study was done to assess awareness among dental undergraduates towards patient safety in different dental institutions of Lahore, Pakistan Methods: It was a cross-sectional analytical study conducted at Combined Military Hospital Lahore Medical College & Institute of Dentistry from 1st May to 30th November, 2020. Two hundred third and fourth year BDS students (149 females and 51males; mean age 21.91±1.08) of 4 dental institutions of Lahore, mostly from private institutions (79.5%) completed Awareness of Patient Safety Questionnaire (APSQIII) to assess awareness of patient safety in dental undergraduates. Data was analyzed through SPSS 21. Results: Teaching and learning about patient safety got the highest item scores while Team functioning got the highest 6.1 mean domain score. Professional incompetence as an error cause got the lowest 3.1 mean score followed by Disclosure responsibility (4.3). No significant difference was seen with respect to gender. Fourth year students were found to be more aware about error disclosure and error reporting confidence with statistically significant difference. All reverse coded items were scored in disagreed range by participants. Conclusion: Despite positive attitudes towards patient safety, lack of awareness was seen in key issues. Incorporation of patient safety in undergraduate curriculum may help in improving patient care and health services.